2021
DOI: 10.11113/aej.v11.18043
|View full text |Cite
|
Sign up to set email alerts
|

Lab-Scale Experiments for Soil Cementing Through Bio-Chemical Process

Abstract: Ureolytic bacteria strains of Bacillus show its ability of calcium carbonate precipitation through metabolic activity. Different studies related to self-healing concrete material were reported associated with the generated calcium carbonate of Bacillus subtilis HU58 metabolism in recent communications. In this paper, recent findings of soil cementing with a combination of such precipitated products were presented. The experiments relied on the lab-scale studies with the use of sand-clay mixture as the controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Furthermore, because the samples’ core zone was tightly restricted, the produced fatigue stresses caused greater damage to the columns of the outer surface, resulting in the advancement of the macropores. Some biocemented specimens have been reported to have similar early surface degradation due to WD forces [ 29 ]. Additionally, the disparity among the heat expansion coefficients between the calcium carbonate and the soil material might be an added element that caused internal fatigue stresses to develop during temperature changes, resulting in carbonate bond degradation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because the samples’ core zone was tightly restricted, the produced fatigue stresses caused greater damage to the columns of the outer surface, resulting in the advancement of the macropores. Some biocemented specimens have been reported to have similar early surface degradation due to WD forces [ 29 ]. Additionally, the disparity among the heat expansion coefficients between the calcium carbonate and the soil material might be an added element that caused internal fatigue stresses to develop during temperature changes, resulting in carbonate bond degradation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the self-healing concrete field has achieved positive results and advancements in recent years in Viet Nam [3,14,63,64]. Laboratory studies, such as those conducted in 2019 and beyond [65,66], have explored the possibility of using Bacillus subtilis (HU58) bacteria for soil cementation. Although the experiments primarily employed small soillike specimens and unconventional approaches, deviating from standardized testing methods in geotechnical engineering, significant findings were obtained, warranting further research in subsequent phases.…”
Section: Case Studies Biocementation In Viet Nammentioning
confidence: 99%